Family-Centered Early Childhood Intervention in Kosovo: Perceptions of Parents - Gyltene Retkoceri Hoxha; Aleksandra Karovska Ristovska (Multidisciplinarni Pristupi u Edukaciji i Rehabilitaciji)
This study investigates the Early Childhood Intervention (ECI) support system in Kosovo, emphasizing the perspectives of families with children experiencing developmental delays and disabilities. Drawing upon the evolution of ECI frameworks since the 1970s, the research highlights the significance of family-centered practices as a primary approach in ECI, as endorsed by the Division for Early Childhood (DEC). Utilizing a descriptive methodology, the study surveyed 89 parents of children aged 0 to 6 who accessed ECI services, focusing on their experiences, barriers encountered, and the effectiveness of current support systems. Results reveal that pediatricians are the most commonly recommended sources for ECI services, with a substantial percentage of families facing waiting lists. The findings underscore the necessity of enhancing advocacy efforts, developing comprehensive national policies, and improving access and coordination of ECI services.